UPAYA MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DI KELAS VII-I SMPN 4 MADIUN - Hilarius Kiswara; Rudi Santoso Yohanes (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2017)
This research aims to increase students’ interest and achievement in mathematics, using cooperative learning model of type Make a Match. The research was conducted from April 23 up to May 3, 2016. The object of this study was the seven-year students of class-I SMPN 4 Madiun in the academic year 2015-2016 (second semester). The total number of the object was 29 students. It is a classroom action research (PTK) performed in 2 cycles. The results of the research showed that the students' interest in learning mathematics increased from the prior (PTK) to cycle I and cycle II. The students' interest in learning mathematics was 26.92% in the prior PTK, 38.46% in the first cycle, and 46.15% in the second cycle. In spite of the increase, the students' interest in learning mathematics has not reached the determined indicators of success, so it needs improving in the next cycle. The students' achievement in learning mathematics increased from the prior (PTK) to cycle I and cycle II. The students’ completion was 38.46% in the prior PTK, 61.54% in the first cycle, and 65.38% in the second cycle. The findings above might arrive at a concusion that cooperative learning model of type Make a Match can increase students’ interest and achievement in mathematics Key words: interest in learning mathematics, achievement in learning mathematics, cooperative learning model of type Make a Match